From an Intangible Idea of a Fashion Collection to an Intangible Digital Future. A Yannis Tseklenis Vase Look Dress - Moyssi, Noly; Georgiou, Ropertos; Avgousti, Avgoustinos (Journal of Greek Archaeology, 2022)
Fashion is defined as changing styles in dress and appearance, adopted by a group of people in a specific place and time; it also relates to the market economy. Roland Gérard Barthes (1915–1980) noted that the annual change in dress code means that the consumer has a new code to learn from year to year, and in this process of learning, fashion magazines have an important role to play. Fashion magazines fulfil this role by combining image with text. Since the 1950s, developing countries with a surplus of unskilled labour were in an advantageous position to attract investments for industrial units that would produce cheap products, as the cheap labour cost of the work hour made them extremely competitive. Developed countries with skilled workforces could only compete with the production of items requiring know-how and high-tech infrastructure if they could justify higher labour costs. These countries, however, had no choice but to import mass-produced goods, produced in developing countries with cheaper labour, such as Greece.